Molecular properties of steroids involved in their effects on the biophysical state of membranes - Wenz, Jorge Javier (2015)
The activity of steroids on membranes was studied in relation to their ordering, rigidifying, condensing and/or raft promoting ability. The structures of 82 steroids were modeled by a semi-empirical procedure (AM1) and 245 molecular descriptors were next computed on the optimized energy conformations. Principal component analysis, mean contrasting and logistic regression were used to correlate the molecular properties with 212 cases of documented activities. It was possible to group steroids based on their properties and activities, indicating that steroids having similar molecular properties have similar activities on membranes. Steroids having high values of area, partition coefficient, volume, number of rotatable bonds, molar refractivity, polarizability or mass displayed ordering, rigidifying, condensing and/or raft promoting activity on membranes higher than those steroids having low values in such molecular properties. After a variable selection procedure circumventing correlation problems among descriptors, area and log P were found as the most relevant properties in governing and predicting the activity of steroids on membranes. A logistic regression model as a function of the area and log P of the steroids is proposed, which is able to predict correctly 92.5% of the cases. A rationale of the findings is discussed.